Molecular Mechanisms of HIV Protease Inhibitors Against HPV-Associated Cervical Cancer: Restoration of TP53 Tumour Suppressor Activities - Makgoo, Lilian; Mosebi, Salerwe; Mbita, Zukile (Frontiers in Molecular Biosciences, 2022)
Cervical cancer is a Human Papilloma virus-related disease, which is on the rise in a number of countries, globally. Two essential oncogenes, E6 and E7, drive cell transformation and cancer development. These two oncoproteins target two of the most important tumour suppressors, p53 and pRB, for degradation through the ubiquitin ligase pathway, thus, blocking apoptosis activation and deregulation of cell cycle. This pathway can be exploited for anticancer therapeutic interventions, and Human Immunodeficiency Virus Protease Inhibitors (HIV-PIs) have attracted a lot of attention for this anticancer drug development. HIV-PIs have proven effective in treating HPV-positive cervical cancers and shown to restore impaired or deregulated p53 in HPV-associated cervical cancers by inhibiting the 26S proteasome. This review will evaluate the role players, such as HPV oncoproteins involved cervical cancer development and how they are targeted in HIV protease inhibitors-induced p53 restoration in cervical cancer. This review also covers the therapeutic potential of HIV protease inhibitors and molecular mechanisms behind the HIV protease inhibitors-induced p53-dependent anticancer activities against cervical cancer.